Dietary Fiber from Mentawai Taro (Colocasia esculenta var. Mentawai) Ameliorates Diabetic Neuropathy in Alloxan-Induced Mice - Safril, Sutri Wulansari; Santoso, Putra; Rahayu, Resti (Biota, 2026)
Diabetic neuropathy is a severe complication of diabetes mellitus, and conventional synthetic drugs used for its management are often associated with undesirable side effects. This study evaluated the potential of Mentawai taro (Colocasia esculenta var. Mentawai) corm as a functional food for the management of diabetic neuropathy. Adult male mice were divided into five groups: a control group (healthy mice fed a standard diet), a diabetic group (alloxan-induced diabetic mice fed a standard diet), and three diabetic groups fed diets supplemented with 15% Mentawai taro corm whole flour, fiber, or starch. After 28 days of dietary intervention, blood glucose levels, sensory and motor functions, malondialdehyde (MDA) levels, and cerebellar histopathology were evaluated. The results showed that Mentawai taro corm fiber significantly reduced blood glucose levels (59.5% reduction), accompanied by a positive trend toward improved sensory responses (25% increase) and a marked enhancement of motor function (41.6% increase) in diabetic mice. Additionally, fiber supplementation reduced MDA levels in brain tissue (19.3% reduction) and attenuated Purkinje cell degeneration in the cerebellum (27.3% reduction). In contrast, Mentawai taro corm whole flour and starch exerted minimal protective effects, with starch supplementation improving motor function only. Overall, among the various Mentawai taro corm preparations tested, the fiber extract was the most effective in ameliorating symptoms of diabetic neuropathy.